Esoteric Zen: Zen and the tantric teachings in premodern Japan - Licha, Stephan (Brill's Japanese studies library, 2023)
Introduction: Three Buddhas Sitting in a Maṇḍala -- 1. Outside the Teachings: Enni, Jōmyō, and the Common Conceptual Space of Zen and Tendai in Early Medieval Japan -- 2. The Vicissitudes of Turning Upward: Enni's Three Mechanisms and Their Contexts -- 3. The Zen of Mahāvairocana: Enni on Zen and the Tantric Teachings -- 4. The Heart of Flesh in the Body of the Teachings: Variations on Esoteric Zen in Enni, Chikotsu, and Kokan -- 5. Means of Mediation: Kōan Interpretation from Enni to Sōtō Lineages -- 6. The Topology of the Womb: Enni, Chikotsu, Dōhan, and the Beginnings of Zen Embryology -- 7. The Womb Was Their Kōan: Zen Embryology in Late Medieval Genjū and Sōtō Lineages -- Conclusions: Tantra, Zen, and Oranges -- Bibliography -- Index.